2017
DOI: 10.1038/onc.2017.136
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone protects hepatocytes from HBx-induced carcinogenesis by enhancing mitochondrial turnover

Abstract: Infection by hepatitis B virus (HBV) accounts for 50-80% of hepatocellular carcinoma (HCC) development worldwide, in which the HBV-encoded X protein (HBx) has critical role in the induction of carcinogenesis. Several studies have shown that thyroid hormone (TH) suppresses HCC development and protects hepatocytes from HBx-induced damage, thus it is of interest to examine whether TH can protect hepatocytes from HBx-induced carcinogenesis. By treating HBx- transgenic mice with or without TH, we confirmed the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 55 publications
3
44
0
Order By: Relevance
“…They further demonstrated that TH abolished HBx-mediated upregulation of transcription factors, phospho-STAT3, c-Jun, NF-κB, and AP-1 through the increase of mROS and the reduction of ∆ψm, and these results are consistent with others reports [35,37,69]. These TH/PINK1/Parkin signaling effects on the reduction of HBx-mediated HCC are correlated with clinical cases [69]. HBx promotes stem/progenitor cell markers in HBx-transgenic mice treated with 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) [70].…”
Section: Hbxsupporting
confidence: 90%
See 4 more Smart Citations
“…They further demonstrated that TH abolished HBx-mediated upregulation of transcription factors, phospho-STAT3, c-Jun, NF-κB, and AP-1 through the increase of mROS and the reduction of ∆ψm, and these results are consistent with others reports [35,37,69]. These TH/PINK1/Parkin signaling effects on the reduction of HBx-mediated HCC are correlated with clinical cases [69]. HBx promotes stem/progenitor cell markers in HBx-transgenic mice treated with 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) [70].…”
Section: Hbxsupporting
confidence: 90%
“…Chi et al investigated the mitochondrial localization of HBx with its effect on mROS and ∆ψm, which correlated with their data from HBx transgenic mice and clinical HBV-mediated HCC patients [69]. HBx-induced carcinogenesis in HBx transgenic mice and predominantly localized into mitochondria in stably expressing HepG2 cells and interacted with PINK1 and parkin [69]. Thyroid hormone (TH) simultaneously induces mitochondrial biogenesis and autophagy of HBx-targeted mitochondria through PINK1 induction to suppress HBx-promoted ROS generation and carcinogenesis [69].…”
Section: Hbxmentioning
confidence: 74%
See 3 more Smart Citations